2021
DOI: 10.3390/ma14237457
|View full text |Cite
|
Sign up to set email alerts
|

Ce-Containing MgAl-Layered Double Hydroxide-Graphene Oxide Hybrid Materials as Multifunctional Catalysts for Organic Transformations

Abstract: The combination of layered double hydroxides (LDH) with graphene oxide (GO) enables the formation of nanohybrids with improved properties. This work focuses on the structural and catalytic properties of Ce-containing MgAl LDH-GO composites bearing different concentrations of GO in the range of 5–25 wt.%. The synthesis of the composites was performed by co-precipitating the LDH phase in the presence of GO, while their characterization was performed using XRF, XRD, DRIFT, Raman, SEM, nitrogen adsorption-desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…The positions of (003), (006) and (009) diffraction peaks for different LDH showed no obvious changes, which indicates that the metal ion and interlayer anion had no effects on the crystalline structure of LDH plate. From the LDH patterns of different metal element compositions, it can be seen that the intensities of the (003) and (006) diffraction peaks of the MgAl–Cl and MgFe–Cl LDH were significantly higher than those of the MgAl–NO 3 and MgFe–NO 3 LDH, indicating that the plate layer crystalline structures of MgAl–Cl and MgFe–Cl LDH were more obvious than those of MgAl–NO 3 and MgFe–NO 3 LDH, which is consistent with the previously reported results [ 37 ]. FTIR spectra ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The positions of (003), (006) and (009) diffraction peaks for different LDH showed no obvious changes, which indicates that the metal ion and interlayer anion had no effects on the crystalline structure of LDH plate. From the LDH patterns of different metal element compositions, it can be seen that the intensities of the (003) and (006) diffraction peaks of the MgAl–Cl and MgFe–Cl LDH were significantly higher than those of the MgAl–NO 3 and MgFe–NO 3 LDH, indicating that the plate layer crystalline structures of MgAl–Cl and MgFe–Cl LDH were more obvious than those of MgAl–NO 3 and MgFe–NO 3 LDH, which is consistent with the previously reported results [ 37 ]. FTIR spectra ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…According to the gradient dilution method, the material concentrations were 5, 10 and 20 μg/mL. Three replicates were used for the experimental group and the control groups [ 37 ]. First, a 2.5 μM live cell fluorescent probe CDCFCA (KeyGEN, China) was added to the medium and cultured in the dark for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…E.g., Ni et al reported the successful effect of REE (Y, La, and Ce) on the performance of Mg/Al (REE) LDH derived catalysts for ammonia synthesis (Ni et al, 2018). The activity of ammonia synthesis was remarkably improved for the catalyst doped with Y. Ce-containing MgAl LDHs with graphene oxide was proposed by Stamate et al as a multifunctional catalyst in two different types of organic transformations: Knoevenagel condensation (cinnamic acid synthesis) and one-pot cascade oxidation-Knoevenagel condensation (2-benzoyl-3phenylacrylonitrile synthesis) (Stamate et al, 2021). Cota et al investigate the catalytic activity of Mg/AlLa LDH derived MO for isomerization of 2,3-dimethyl-1-butene to 2,3-dimethyl-2-butene (Cota et al, 2016).…”
Section: Catalytic Activitymentioning
confidence: 99%
“…A series of publications reported the use of MgAl-LDH NPs deposited on various nanocarbons (CNF, MWCNT, or GO) as solid base catalysts for the self-condensation of acetone, the single-stage synthesis of MIBK, the Claisen-Schmidt condensation of acetophe-none and benzaldehyde, the Knoevenagel reaction, and the transesterification of glycerol with diethyl carbonate [13,14,20,37,44,[59][60][61].…”
Section: Base and Multi-step Reactionsmentioning
confidence: 99%
“…Recently, Ce-containing MgAl-LDH-GO composites bearing different GO loading (5-25 wt%) were tested as catalysts in the Knoevenagel condensation of benzaldehyde with dimethyl malonate to diethyl benzylidene malonate (DBM) and subsequently to cinnamic acid (CNA), and the one-pot cascade oxidation-Knoevenagel condensation of benzyl alcohol (BA) and benzoyl acetonitrile to yield 2-benzoyl-3-phenylacrylonitrile (BPA) [61]. The Ce-MgAl-LDH/GO composite prepared by coprecipitation (Table 2, entry 9) presented the typical structural features corresponding to both LDH and GO.…”
Section: Knoevenagel and One-pot Oxidative Knoevenagel Reactionsmentioning
confidence: 99%